Lewis Acid Chemistry of Some Sulphur-Nitrogen Compounds - Tyrer, David John (My University, 1978)
The compound S₄N₄ has been shown to react with the Lewis acids SbCl₅, SbF₅ and AsF₅ to produce the previously unreported cyclotetra-thiazyl dication, S₄N₄²⁺, in the form of the salts S₄N₄(SbCl₆)₂, S₄N₄(SbF₆)₂, S₄N₄(AsF₆)₂.xSO₂ and S₄N₄(Sb₃F₁₄)(SbF₆). A reaction sequence for the preparation of S₄N₄(SbCl₆)₂ has been suggested and the infrared and Raman spectra for each of the salts is reported as well as the crystal structures of the S₄N₄(SbCl₆)₂ and S₄N₄(Sb₃F₁₄)(SbF₆) salts.
A brief investigation of the reaction of S₄N₄ with the Lewis acids PF₅ and PCl₅ produced in the S₄N₄/PF₅ system the new molecular adduct, S₄N₄PF₅, whereas the reaction of S₄N₄ with PCl₅ yielded a complex mixture of products, composed of phosphonitrilic chlorides.
The chemistry of trichlorocyclotrithiazene with SbCl₅ has been studied. It has been determined for the first time that S₃H₃Cl₃ when oxidized by SbCl₅ produces the S₄N₄(SbCl₆)₂ salt with the compounds S₄N₄ SbCl₅ and S₅N₅ (SbCl₆) isolated as intermediates formed during the production of the S₄N₄²⁺ dication. The crystal structures of both Si₄N₄ SbCl₅ and S₅N₅(SbCl₆) are reported in this thesis.
In contrast, the fluoride, trifluorocyclotrithiazene, S₃N₃F₃, when combined with the Lewis acids SbF₅, AsF₅ and SO₃ was not oxidized but rather simple fluoride ion abstraction occurred to yield the thiazyl salts SN(Sb₂F₁₁), SN(AsF₆) and SN(SO₃F).
For the first time, the chemistry of the sulphur imides with Lewis acids of oxidative capability has been studied.
Cyclotetrasulphurtetraimide, S₄N₄H₄, reacted readily with SbCl₅ to yield the S₄N₄²⁺ salt, S₄N₄(SbCl₆)₂. The compound S₄N₄ SbCl₅ has been shown to be an intermediate formed during the oxidation of S₄N₄H₄ with SbCl₅.
Cycloheptasulphurimide, S₇NH, and 1,4-cyclohexasulphurdiimide, 1,4-S₆N₂H₂, produced the previously unknown dithionitronium ion, S₂N⁺, when treated with SbCl₅. Infrared and Raman spectra for the S₂N(SbCl₆) are reported as well as the crystal structure.
In a limited investigation, the compound Cl₃PNPCl₃(PCl₆), has been isolated from the reaction of S₇NH with PCl₅. The crystal structure of the trichlorp[(trichlorophosphoranylidene)amino] phosphorus (V) hexachlorophosphate is reported in this work.
Keywords: Chemistry; Chemistry